The encyclopedia of Christian literature. Volume 2, Biographies H-Z - Kurian, George Thomas; Smith, James D., 1951 January 12- (Lanham, Md. : Scarecrow Press, 2010)
Covering 2,000 years, The Encyclopedia of Christian Literature is the first encyclopedia devoted to Christian writers and books. In addition to an overview of the Christian literature, this two-volume set also includes 40 essays on the principal genres of Christian literature and more than 400 bio-bibliographical essays describing the principal writers and their works. These essays examine the evolution of Christian thought as reflected in the literature of every age. The companion volume also features bibliographies, an index, a timeline of Christian Literature, and a list of the greatest Christian authors. --from publisher description.
V. 1. Genres and types / Biographies A-G -- v. 2. Biographies H-Z.
Includes bibliographical references and index.
Print version record.
Keywords: Christian literature -- Encyclopedias; RELIGION -- Christianity -- Literature & the Arts; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Christian literature; Electronic books; Encyclopedias